PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIA SMP AN-NAMIROH PEKANBARU - Tarhan, Hatun; Solfitri, Titi; ', H. Zuhri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to improve the learning process and increase the student’s mathematics learning outcomes through the implementation Cooperative Learning of STAD. This type of research is the Classroom Action Research with two cycle. The research was conducted in class VIIA SMP An-Namiroh Pekanbaru in the odd semester of the 2016/2017 academic year with the subject of as many as 29 students, consist of 14 boys and 15 girls. The research instrument consists of learning devices and instrument data collectors. Learning device used in this research is the Syllabus, Lesson Plan and Worksheet. The instrument data collector used in this research is the observation sheet and math achievement test. Data analysis technique used is descriptive statistical analysis. Based on the result of the research showed that implementation of learning process on cycle II had happened improvement from implementation on cycle I. Weakness on cycle I is improved on implementation cycle II according with planning of improvement after reflection cycle I. Number of students that reach Minimum Mastery Criteria increase from basic score to daily test II. The number of students who reach Minimum Mastery Criteria on basic scor, daily test I and daily test II are respectively 14 person (48%), 16 person (55%) and 20 person (69%). Results of this research indicates that application of Cooperative Learning of STAD can improve learning process and increase mathematics learning outcomes from the students at class VIIA SMP An-Namiroh Pekanbaru in the odd semester academic years 2016/2017 at Basic Competencies 2.1 Knowing the algebra and it’s elements, and 2.2 Doing algebra operation.Key words: Cooperative Learning of STAD, student’s mathematics learning outcomes, Classroom Action Research